A CLINICAL STUDY TO EVALUATE THE EFFICACY OF VASADI YOGA IN THE MANAGEMENT OF RAKTAPRADAR (International Journal of Ayurveda and Pharma Research, 2020)
Raktapradar is a most common gynecological problem found in PTSR. It is not a disease but a symptom found in many gynaecological disorders. Most of the gynaecological disorder comes under the heading of Yonivyapad in Ayurvedic classics. It has an associated complication like Pandu and sterility. Hence Vasadi churna with Tandulodak is chosen to study its effect in Raktapradar. Method: A clinical trial was conducted in indoor and outdoor patient diagnosed with Raktapradar. The 30 patient was given with an Ayurvedic drug and monitored according to protocol including clinical and pathological parameter. The criteria for selection of patient are inclusive and exclusive. Patient from inclusive criteria have excessive bleeding p/v was selected. Clinical symptoms were assessed with four grades as follow no change, marked, moderate, and severe. Criteria for assessment were marked, moderate and mild. Results: Results were noted and it was observed that selected drug is safe and effective.